Rapid publication and broad communication of Soil Organisms - Monica A. Farfan; Anton Potapov; Nico Eisenhauer (Soil Organisms)
Soil ecology has become a highly dynamic field of research. This requires not only the rapid publication of scientific findings, but also the broad communication of their implications. At Soil Organisms, we now introduce two major developments that are intended to facilitate both tasks and consolidate the journal as a unique outlet in soil ecology.